Heavy metals induce phosphorylation of the Bcl-2 protein by Jun N-terminal kinase - Ondroušková, Eva; Slováčková, Jana; Pelková, Vendula; Medalová, Jiřina; Souček, Karel; Beneš, Petr; Šmarda, Jan (Biological chemistry, 2009)
The Bcl-2 protein is one of the key components of biochemical pathways controlling programmed cell death. The function of this protein can be regulated by posttranslational modifications. Phosphorylation of Bcl-2 has been considered to be significantly associated with cell cycle arrest in the G2/M phase of the cell cycle, and with cell death caused by defects of microtubule dynamics. This study shows that phosphorylation of Bcl-2 can be induced by heavy metals due to activation of the Jun N-terminal kinase pathway that is not linked to the G2/M cell cycle arrest. Furthermore, we demonstrate that hyperphosphorylated Bcl-2 protein is a more potent inhibitor of zinc-induced cell death than its hypophosphorylated mutant form. These data suggest that regulation of Bcl-2 protein function by phosphorylation is an important part of cell responses to stress.
Keywords: regulace genové exprese u nádorů; financování organizované; Animals; Stress, Physiological; posttranslační úpravy proteinů; apoptóza; JNK Mitogen-Activated Protein Kinases; Cell Line, Tumor; Apoptosis; Gene Expression Regulation, Neoplastic; lidé; Proto-Oncogene Proteins c-bcl-2; Zinc; protoonkogenní proteiny c-bcl-2; signální transdukce; Protein Processing, Post-Translational; Electrophoresis; Signal Transduction; elektroforéza; fyziologický stres; Phosphorylation; JNK mitogenem aktivované proteinkinasy; zinek; Financing, Organized; fosforylace; těžké kovy; zvířata; Metals, Heavy; nádorové buněčné linie; Humans